EFEKTIFITAS KEGIATAN KELOMPOK SIMPAN PINJAM KHUSUS PEREMPUAN DI KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Gianina Amelinda Rantung; Lyndon R.J. Pangemanan; Charles R. Ngangi; Ellen G. Tangkere (COCOS, 2014)
ABSTRACTThis research has been purposed to describe the effectiveness of Savings and Loans For Woman Group Activity (SPP) in Kauditan Subdistrict North of Minahasa Regency on 2012-2013. The benefit of this research is to provide information about the effectiveness of activity operated by saving and loans for woman group in Kauditan Subdistrict North of Minahasa Regency and to give an information to those who need that information.Data collected are primary data and secondary data. The primary data was obtained by distributing questionnaires to respondents and the secondary data was obtained from the institutions associated with this research. The sampling method was done by "cluster sampling". The selected respondents were all members of savings and loans for woman group. The total sample is 30 members of savings and loans special for woman group.The results of this research showed that the effectiveness of savings and loans for woman group activity in Subdistrict Kauditan relatively effective with a percentage of 93%. It means that all members of the group used the funds for productive activities by adding capital to business in order to further develop the business.